Optimization and Analysis of Structure about Lifting Device of Logistics Sorting - Zhao, G; Tiba, Zsolt; Menyhárt, József (International Journal of Engineering and Management Sciences, 2019)
The lifting device of a logistics sorting machine needs high frequency upward and downward reciprocating motion therefore the cutting fork arms and matching parts of the shaft are often worn out. In this paper the problem of the shear fork types applied for the lifting mechanism is studied at first. Then the advanced numerical simulation software ANSYS adopted for the lifting mechanism of the shear fork type, and the means of virtual simulation is introduced. Hence the possible location of faults and fault modes are analysed. Then improving measures about the lifting mechanism of the logistics sorting machine are suggested.